(3GdeYLRGJ GdfLjHjI aj TQM GdQSGdI GdYdGFjI aj GdMSGHs - (3LdGd GdOjf Ydj Hf GdZQHis; (3eMeO Hf ehSi GdSHcjs ((3CMeO Hf Ydi Hf YfHg GdMSjfi GdOGhhOi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdebOS HLdGdg Yf GdYOO s
(3BNQgG (B:s
(3hBJfi cJGHi Hjejfi jhe GdMSGH , hgH di ef dOjc QMeI s
(3hGdQSGdI GdYdGFjI ef JCdja eMeO Hf eUOb GdUaOi GdJQcSJGfi GdeJhai SfI (B712(3g` s
(3HQSe NRGfI GdCejQ ZjGK GdGSe eMeO Hf MSjf GdQOeZGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs